Lexicons and Their Cultural Meanings Found in the Tutug Kambuhan Ritual in Menyali Village - Seniasih, Ni Kadek Mira; Budasi, I Gede; Rismadewi, Ni Wayan Monik (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
Tutug Kambuhan is a sacred ritual to celebrate a 42-day-old baby. As one of the cycles in Manusa Yadnya, Tutug Kambuhan has many traditional terms in its procedures. However, some of the younger generation rarely know about it and it has the potential to be eroded along with the times (language death). So far there has been no research that discusses the lexicon in the Tutug Kambuhan ritual, especially in Menyali Village. This research aims to identify the lexicons contained in the procedure of Tutug Kambuhan Ritual in Menyali Village and analyze its cultural meaning. This research focuses on two things, namely the lexicons contained in the Tutug Kambuhan ritual procedure and the cultural meaning of the lexicons. This research uses a qualitative method and an ethnolinguistic approach. This research uses 4 instruments, namely the researcher, interview guidelines, notes, and recording devices. Data collection was done by observation and in-depth interviews with a snowballing technique. Data analysis used includes 4 stages as suggested by Miles and Huberman (1994) including data collection, data reduction, data display, and conclusion. In the results of this study, a total of 38 lexicons were identified in the Tutug Kambuhan procedure in Menyali Village. The findings include: ngulemin, jro mangku, penguleman, sesari, sanggah kemulan, ngalih dauh, nyapatin/ngaluang, sutri, megarapan, banten, srati, mabanyuawangan, pelinggih, mapiuning, penglingsir, natab, dedinan, ngayab, soda, sagi, raka, pelangkiran, ngeluarang, pasegoan, nasi warna, ganjaran, ari-ari, pejati, canang sari, mapetinget-tinget, metaken-taken, piuning, pesarean, nyeroadi, banyuawang, maturan, meraosan, and jro gede.  The results of this study have implications for the provision of cultural heritage documents and increased insight into the field of Linguistics in education.